Temporal pattern of Borrelia burgdorferi p21 expression in ticks and the mammalian host. - Das, S (1997)
The temporal synthesis of the P21 protein of Borrelia burgdorferi and the development of the humoral response to this antigen was assessed in infected mice. p21 is a member of the ospE-F gene family and its protein, P21, has been shown to be expressed by B. burgdorferi within infected mice but not by spirochetes cultured in vitro. P21 was not detected on B. burgdorferi in unfed or engorged Ixodes dammini (also known as I. scapularis) ticks, further supporting the postulate that P21 synthesis is specific for the mammalian host. In B. burgdorferi-infected mice, ospE mRNA and OspE antibodies were observed at 7 d, whereas p21 mRNA and P21-specific antibodies were detected at 21-28 d, suggesting that p21 is expressed later than ospE. Moreover, ospA mRNA was not discernible until day 14, indicating that ospA, like p21, is not expressed in the early stages of tick-transmitted murine Lyme borreliosis. Because p21 is expressed during infection in mice, we assessed the human humoral response to P21. 28% (34 of 122) of the patients with either early- or late-stage Lyme disease, and 33% (11 of 33) of the individuals with Lyme arthritis had P21 antibodies, suggesting that a P21 response may serve, at least partially, as a marker of infection. Active immunization with recombinant P21 did not protect C3H mice from tick-borne B. burgdorferi infection, and passive transfer of P21 antiserum to infected mice did not alter the course of disease. These data suggest that the antigenic structure of B. burgdorferi changes during the early stages of murine infection.